Human iPSC-Based Models for the Development of Therapeutics Targeting Neurodegenerative Lysosomal Storage Diseases - Luciani, Marco; Gritti, Angela; Meneghini, Vasco (Frontiers in Molecular Biosciences, 2020)
Lysosomal storage diseases (LSDs) are a group of rare genetic conditions. The absence or deficiency of lysosomal proteins leads to excessive storage of undigested materials and drives secondary pathological mechanisms including autophagy, calcium homeostasis, ER stress, and mitochondrial abnormalities. A large number of LSDs display mild to severe central nervous system (CNS) involvement. Animal disease models and post-mortem tissues partially recapitulate the disease or represent the final stage of CNS pathology, respectively. In the last decades, human models based on induced pluripotent stem cells (hiPSCs) have been extensively applied to investigate LSD pathology in several tissues and organs, including the CNS. Neural stem/progenitor cells (NSCs) derived from patient-specific hiPSCs (hiPS-NSCs) are a promising tool to define the effects of the pathological storage on neurodevelopment, survival and functionality of neurons and glial cells in neurodegenerative LSDs. Additionally, the development of novel 2D co-culture systems and 3D hiPSC-based models is fostering the investigation of neuron-glia functional and dysfunctional interactions, also contributing to define the role of neurodevelopment and neuroinflammation in the onset and progression of the disease, with important implications in terms of timing and efficacy of treatments. Here, we discuss the advantages and limits of the application of hiPS-NSC-based models in the study and treatment of CNS pathology in different LSDs. Additionally, we review the state-of-the-art and the prospective applications of NSC-based therapy, highlighting the potential exploitation of hiPS-NSCs for gene and cell therapy approaches in the treatment of neurodegenerative LSDs.